Brain structural and functional correlates of resilience to Bipolar Disorder - Frangou, Sophia (Frontiers in Human Neuroscience, 2012)
Background: Resilient adaptation can be construed in different ways, but as used here it refers to the adaptive brain changes associated with avoidance of psychopathology despite familiar risk for Bipolar Disorder (BD). Although family history of BD is associated with elevated risk of affective morbidity a significant proportion of first-degree relatives of BD patients remains free of psychopathology. Examination of brain structure and function in these individuals may inform on adaptive changes that may pre-empt disease expression. Methods: Data presented here are derived from the Vulnerability to Bipolar Disorders (VIBES) study which includes patients with BD, asymptomatic relatives and healthy controls. Participants underwent extensive investigations including brain structural (sMRI) and functional magnetic resonance imaging (fMRI). The data presented here focus on sMRI voxel-based-morphometry and on conventional and connectivity analyses of fMRI data obtained during the Stroop Colour Word Test (SCWT), a task of cognitive control during conflict resolution. All analyses were implemented in SPM (www.fil.ion.ucl.ac.uk/spm). Resilience in relatives was operationalized as the absence of clinical-range symptoms. Results: Resilient relatives of BD patients expressed structural, functional and connectivity changes reflecting the effect of genetic risk on the brain. These included increased insular volume, decreased activation within the posterior and inferior parietal regions involved in selective attention during the SCWT, and reduced fronto-insular and fronto-cingulate connectivity.Resilience was associated with increased cerebellar vermal volume and enhanced functional coupling between the dorsal and the ventral prefrontal cortex. Conclusions: Our findings suggests the presence of biological mechanisms associated with resilient adaptation of brain networks and pave the way for the identification of outcome-specific trajectories given a particular genotype.